Violência Política: do Estado à Subversão do Estado - Análise sobre um Modelo Conceptual - Duarte, Felipe Pathé (2012)
This is a conceptual, anthological and descriptive article. We will refer to the problems of the theoretical forum related to the definition of violence and associate it not only with the exercise of power but with its overthrow. We expose it from a dialectical perspective. First, violence is analyzed as a form of constitution of the state; secondly as a form of state maintenance; and, lastly, as a form of state destruction. In other words, in the first two perspectives, violence is seen as an institutional element, and in the last one it is analyzed as a way to challenge that same institutional dimension. Thus we enter the field of subversion. The article refers to conceptual representations that see violence as an instrumental dimension, structured or unstructured, guaranteeing a possible political transformation or subsistence, either at the institutional or non-institutional level. Thus we speak of violence as a continuation of politics, but by other means. Resumo Este é um artigo conceptual, antológico e descritivo. Referir-nos-emos aos problemas do foro teórico relacionados com a definição de violência e associamo-la não só ao exercício do poder como à sua derrocada. Expomo-la aqui de uma perspectiva dialéctica. Em primeiro é analisada  a vioência como forma de constituição de Estado; em segundo como forma de manutenção de Estado; e; por último, como forma de destruição de Estado. Ou seja, nas duas primeiras perspectivas a violência é vista como um elemento institucional, para na última ser analisada como forma de pôr em causa essa mesma dimensão institucional. Assim entramos no campo da subversão. O artigo refere-se a representações conceptuais que vêem na violência uma dimensão instrumental, estruturada ou não-estruturada, garante de possível transformação ou subsistência política, quer ao nível institucional ou não-institucional. Falamos assim da violência como continuação da política, mas por outros meios.